一种基于多区域感知的人脸部位定位方法、装置及介质 (2025)
本发明公开了一种基于多区域感知的人脸部位定位方法、装置及介质，涉及图像处理技术领域，包括步骤：提取输入图像中人脸区域的矩形边界图像，并基于人脸关键点对矩形边界图像中的人脸区域进行子区域划分；通过提取各子区域的多尺度特征并进行交互优化，构建子区域间的几何关系和特征关联性模型的构建；以构建的模型为先验知识，通过递归式特征金字塔进一步融合和优化多尺度特征；以融合后的特征为主检测头的输入，以融合前的特征为辅检测头的输入，通过双检测头架构进行人脸部位的定位。本发明确保了人脸区域的精准定位和划分，提高了检测精度，还提升了系统在复杂场景下的鲁棒性。 The invention discloses a face part positioning method and device based on multi-region perception and a medium, and relates to the technical field of image processing, and the method comprises the steps: extracting a rectangular boundary image of a face region in an input image, and carrying out the sub-region division of the face region in the rectangular boundary image based on face key points; by extracting multi-scale features of each sub-region and performing interactive optimization, constructing a geometrical relationship between the sub-regions and constructing a feature relevance model; further fusing and optimizing multi-scale features through a recursive feature pyramid by taking the constructed model as priori knowledge; the fused